Biomonitoramento de trabalhadores de curtume ocupacionalmente expostos a misturas químicas contendo Cromo III através da mensuração de Cromo na urina e do ensaio cometa em Teresina - PI - Rodrigues, Ítalo Sávio Mendes (2014)
Occupational exposure in tanning environments has been the subject of study and scientific research. The controversial information on the toxicity of chrome III and its relation to the epidemiology of tannery served as input for this search. The aim of this study was to evaluate the possible genotoxic effects of exposure of tannery workers Teresina (PI) to chemicals containing chrome III by comet test and measurement of chrome in the urine. This is a transversal, observational and quantitative research. Samples of blood and urine of 43 workers tannery for comet analysis in lymphocytes (43 workers) and chrome in the urine (27 workers) were collected. The same analyzes were performed on workers not exposed to the tannery environment for statistical comparison. In addition, a personal health questionnaire recommended by the International Comission for Protection Against Environmental Mutagens and Carcinogens-ICPEMC aiming to correlate their information to the data obtained in the tests was applied. The results indicated significant increases (tukey-ANOVA p <0.05) for all classes of damage and frequency of damage in the comet assay in lymphocytes of tannery workers compared to unexposed. The chrome in the urine indicated that the workers were the highest concentration of this metal in urine that non-exposed (p <0.05) (1.108 ± 1.277 vs 0.089 ± 0.027). A correlation (Pearson) between the chrome in the urine and genotoxic analyzes indicated strong positive relation with damage class 3:04. It is concluded that the employees of the tannery higher risk of toxicity and genetic instability associated with occupational exposure to chemical mixtures containing chrome III.